A possible risk of CAD/CAM-produced composite resin premolar crowns on a removable partial denture abutment tooth: a 3-year retrospective cohort study. Issue 1 (January 2019) - Miura, Shoko; Kasahara, Shin; Yamauchi, Shinobu; Katsuda, Yusuke; Harada, Akio; Aida, Jun; Egusa, Hiroshi
Abstract: Purpose: To evaluate the early performance of computer-aided design/computer-aided manufacturing (CAD/CAM)-produced composite resin crown (CAD/CAM composite crown) treatment on premolars, specifically, placement on a removable partial denture (RPD) abutment tooth, and the distalmost tooth in the dental arch, as possible clinical risk factors. Methods: A retrospective cohort study (April 2014 to July 2017) was performed utilizing the clinical records of patients who received a premolar CAD/CAM composite crown treatment. The variables of time of treatment for (1) successful crowns (complication event-free) and (2) surviving crowns (clinically functional including re-luted) were estimated using Kaplan–Meier analysis. Survival distributions regarding "RPD abutment tooth" and "distalmost tooth" were analyzed with the log-rank test. Multilevel survival analyses were used to identify hazard ratios and associated risk factors. Results: Five hundred and forty-seven crowns were evaluated (mean follow-up time 1.3 ± 0.9 years) in 327 patients. A total of 87 crowns had at least one complication, with loss of crown retention being the most common (70 crowns). Estimated success and survival rates at 3 years were 71.7% and 96.4%, respectively. The risk of complications was significantly higher for an RPD abutment tooth than for a non-RPD abutment tooth. There was no significant difference between the distalmost tooth and non-distalmost tooth in the dental arch. Conclusions: The demonstrated complication rate for CAD/CAM composite crowns placed on premolars was 15.9% over a period of up to 3 years. There was a substantial risk of complications with placement of such a crown on an RPD abutment tooth.